COMPARATIVE EVALUATION OF ANTIOXIDANT EFFECT OF HERBAL PRODUCT AND SYNTHETIC METHIONINE IN BROILERS - SEEMA. D.M,; JAGADEESH S. SANGANAL,; R. RASHMI, (International Journal of Pharma and Bio Sciences, 2015)
Antioxidant effect of Herbal product and Synthetic Methionine was evaluated in broilers. Six groups containing 12 birds in each group. Group I served as control fed with basal diet deficient with methionine. Group II served as toxic control fed with cadmium chloride at 100 ppm. Group III and IV served as positive control fed with Methiorep® at 1.4 g/kg diet and synthetic methionine at 1.2 g/kg diet respectively. Group V and VI fed with cadmium chloride at 100 ppm upto 4 week for inducing oxidative stress, followed by Methiorep® at 1.4 g/kg diet and synthetic methionine at 1.2 g/kg diet respectively for next 2 week. Cadmium fed groups showed significantly increased level in biochemical parameters and oxidative stress marker, Thiobarbituric acid reactive substances and antioxidant enzyme i.e superoxide dismutase level and significantly decreased level in glutathione and performance parameters indicating cadmium induced oxidative damage on several organs. Histopathology of cadmium fed groups revealed the toxic effect of cadmium on liver, kidney and spleen. Supplementation of the herbal product and synthetic methionine showed improvement in all the above discussed parameters.